Prospective Study Reveals Host Microbial Determinants of Clinical Response to Fecal Microbiota Transplant Therapy in Type 2 Diabetes Patients - Ding, Dafa; Yong, Huijuan; You, Na; Lu, Wei; Yang, Xu; Ye, Xiaolong; Wang, Yayun; Cai, Tingting; Zheng, Xiaoling; Chen, Hui; Cui, Bota; Zhang, Faming; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Increasing evidence shows that alterations in gut microbiome (GM) contribute to the development of type 2 diabetes mellitus (T2DM), and fecal microbiota transplantation (FMT) successfully treats various human diseases. However, the benefits of FMT therapy to T2DM patients remains unknown. Methods: We enrolled 17 patients with T2DM for non-blinded, one-armed intervention trial of FMT. And 20 healthy individuals were recruited as baseline control. HbA1c% and metabolic parameter change were evaluated in 17 T2DM patients 12 weeks after they received FMT from healthy donors. The GM composition was characterized by 16S rRNA gene amplicon sequencing from faecal samples prior to and 12 weeks after FMT treatment. Results We found that the GM of T2DM patients were reconstituted by FMT. We observed a statistically significant decrease in HbA1c% (from 7.565 ± 0.148 to 7.190 ± 0.210, p<0.01), blood glucose (from 8.483 ± 0.497 to 7.286 ± 0.454 mmol/L, p<0.01) and uric acid (from 309.4 ± 21.5 to 259.1 ± 15.8 µmol/L, p<0.01) while a significant increase in postprandial C-peptide (from 4.503 ± 0.600 to 5.471 ± 0.728 ng/ml, p<0.01) at 12 weeks after FMT. Closely evaluating the changes in these assays, we found individual variability in response to FMT treatment. 11 of 17 T2DM patients were found to significantly improve T2DM symptoms. The FMT responders have significantly higher levels of family Rikenellaceae and genus Anaerotruncus (family Ruminococcaceae) in their pretreated fecal in comparison to non-responders, which could predict the clinical response with area under curve of 0.83. Conclusion: Our findings suggest that certain T2DM patients can potentially benefit from FMT and the pretreated abundance of Rikenellaceae and Anaerotruncus in the fecal of patients may serve as potential biomarkers for selecting T2DM patients to receive FMT.